2016
DOI: 10.1177/1097184x16634798
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the Male Body Attitudes Scale (MBAS) among Spanish Adolescent Males

Abstract: The aim of this study was to examine the factor structure of the Male Body Attitudes Scale (MBAS) among a sample of 212 adolescent males by conducting a confirmatory factor analysis. The data revealed that while muscularity and low body fat factors were appropriate for the male sample, the height factor was not supported. The composite MBAS-Spanish version (MBAS-S) and its two factors had high internal consistency and were not significantly related to the traditionally used measure of body image (Eating Disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
14

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 39 publications
4
14
0
14
Order By: Relevance
“…The two-factor, 22-items version used (Sepúlveda et al, 2014) is consistent with previous recommendations on the original factor structure (Blashill & Vander Wal, 2009), and shows excellent levels of internal consistency. In this case, the current sample presented higher scores than the original Spanish sample (Sepúlveda et al, 2014) on the MBAS-S LBF, but no differences were observed among the MBAS-S M scores.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The two-factor, 22-items version used (Sepúlveda et al, 2014) is consistent with previous recommendations on the original factor structure (Blashill & Vander Wal, 2009), and shows excellent levels of internal consistency. In this case, the current sample presented higher scores than the original Spanish sample (Sepúlveda et al, 2014) on the MBAS-S LBF, but no differences were observed among the MBAS-S M scores.…”
Section: Discussionsupporting
confidence: 71%
“…The two-factor, 22-items version used (Sepúlveda et al, 2014) is consistent with previous recommendations on the original factor structure (Blashill & Vander Wal, 2009), and shows excellent levels of internal consistency. In this case, the current sample presented higher scores than the original Spanish sample (Sepúlveda et al, 2014) on the MBAS-S LBF, but no differences were observed among the MBAS-S M scores. Because of the aforementioned similarities between the current sample and the Spanish sample (Sepúlveda et al, 2015) on the DMS-S scores, it is no surprise that they also show similar results in the MBAS M, since they all assess the desire to become more muscular.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations